2023
DOI: 10.1002/ecy.3974
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of bipartite network analyses to incomplete sampling and taxonomic uncertainty

Abstract: Bipartite network analysis is a powerful tool to study the processes structuring interactions in ecological communities. In applying the method, it is assumed that the sampled interactions provide an accurate representation of the actual community. However, acquiring a representative sample may be difficult as not all species are equally abundant or easily identifiable. Two potential sampling issues can compromise the conclusions of bipartite network analyses: failure to capture the full range of interactions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…For the same reason, at the species level, only the results for the coscoroba swan may be taken with caution, while those for the remaining species will likely be robust. The effect of sample size for bipartite networks has recently been evaluated by Llopis-Belenguer et al (2022), finding that the categorical (but not the quantitative) classification of networks in nestedness and modularity is robust to a reduced sample size.…”
Section: Discussionmentioning
confidence: 99%
“…For the same reason, at the species level, only the results for the coscoroba swan may be taken with caution, while those for the remaining species will likely be robust. The effect of sample size for bipartite networks has recently been evaluated by Llopis-Belenguer et al (2022), finding that the categorical (but not the quantitative) classification of networks in nestedness and modularity is robust to a reduced sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, questions of determination level are less important, since the same precision has been maintained for all samples. Furthermore, studies on interaction networks have shown that the level of determination of specimens has little effect on network characteristics, provided that this level of determination does not fall below too high a threshold (Llopis-Belenguer et al 2023; Renaud et al 2020).…”
Section: Discussionmentioning
confidence: 99%